Reduksi Kejenuhan Belajar Sejarah Kebudayaan Islam; Analisis Variasi Metode dan Media Pembelajaran Berbasis Digital - Siddik, Mhd. Fajar; Mahariah, Mahariah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to determine the emergence of learning obstacles experienced by students at MAS PAB 4 Klumpang. This research uses qualitative methods with the type of field research and descriptive methods. Data collection by observation, interviews, and documentation. This study produced several findings, namely: (1) Factors causing saturation of learning SKI (History of Islamic Culture) experienced by grade XI students include: experiencing fatigue in the body due to carrying out routine activities, fatigue felt by limbs such as fingers and toes due to a lot of writing, looking weak and there are students who put their heads on the table when the teacher is explaining due to the teacher's lack of attention to Students, experiencing lazy learning due to food intake that is not good for the body and the absence of effective methods carried out by teachers. (2) Variations of digital-based learning methods and media in reducing SKI learning saturation by Giving Assignments to Students, Increasing Teacher Attention to Students, Learning Outside the Classroom, Adding Reading Resources or SKI Learning References (3) Learning achievement with a variety of digital-based learning methods and media in MAS PAB 4 Klumpang schools. Personalized Learning, Breadth of Information, More Interesting Lessons,  Develop Accountability, Learning Flexibility, Recorded Content, 24-Hour Resources, Connected Learning, Easily Track Student Progress, and Improve Written Language Skills.